Women access to household and farm resources in Sunamganj haor area of Bangladesh - Yeasmin, Farhana; Miah, Md Abdul Momen; Rahman, M Hummadur; Shamim, Md Showkot Osman (Annals of Bangladesh Agriculture, 2023)
In this present investigation the access of women to their household and farm resources were exmined in Sunamganj haor areas of Bangladesh. Data were collected using a structured questionnaire from November 2016 to March 2017 through face-to-face contact with 200 sampled respondents who were selected following simple random sampling method. Access of woman to household and farm resources was measured based on their extent of access to those two selected resources -, each resource comprising 22 items. The findings of the study revealed that 49% of the respondents had low access and 51% had medium access to household resources. Twenty-nine percent of the women had low access whereas 71% of the women having medium access to farm resources. Thirty-nine percent of the haor women had low access and 61% having medium access to overall resources. None of the haor women was found with higher access to mutual household and farm resources. The finding indicated that the majority of the women were deprived of having power and authority to use and control over the household resources and they were also lagged behind in respect to use and control over farm resources. In addition, out of fourteen attributes, five attributes, namely, education, household farm size, role in family decision-making, availability of household resources, and availability of farm resources had significant influence on the access to resources of women in the haor area. Finally, it is concluded that the findings of the study can be utilized by the policymakers and planners of the country to formulate future plan of haor women to improve their livelihood and empowerment. Ann. Bangladesh Agric. 27(2):145-159